Jejak Politik dan Perjuangan Bung Karno - Darma Laksana, I Ketut (Pustaka : Jurnal Ilmu-Ilmu Budaya; Vol 19 No 2 (2019)DO - 10.24843/PJIIB.2019.v19.i02.p03, 2019)
Understanding of Soekarno / Bung Karno must be done thoroughly. This political figure and independence proclamator has established himself as a respected person in the world. That is why, as many as twenty-six titles of Doctoral Causa were awarded to Bung Karno who came from renowned universities in the world. However, behind all that, during the occupation, Bung Karno went in and out of prison. Still as a detainee at Sukamiskin Prison (1926), Sukarno underwent a trial by filing a plea titled Indonesia Menggugat in Lanraad Building, Bandung. The interesting thing in his plea was that the target was not only directed at the judges who were convening it, but also outside parties, especially the Dutch who were perpetrators of imperialism. He reminded the Netherlands that he was not a rebel, but someone who wanted to claim his right to independence. Prison, seizing independence, the PRRI-Permesta rebellion, liberation of West Irian, confrontation with Malaysia, and the rebellion of the G 30 S / PKI, are historical facts that characterize his struggle. To reveal all this, the data of this paper comes from various sources, which are generally understood by the public, especially the educated. Thus, methodologically, this paper is a historical retrospection, looking back at the traces of politics and the struggle of Bung Karno.